Perioperative Anemia: Prevention, Diagnosis, and Management Throughout the Spectrum of Perioperative Care. (May 2020) - Warner, Matthew A.; Shore-Lesserson, Linda; Shander, Aryeh; Patel, Sephalie Y.; Perelman, Seth I.; Guinn, Nicole R.
Abstract : Anemia is common in the perioperative period and is associated with poor patient outcomes. Remarkably, anemia is frequently ignored until hemoglobin levels drop low enough to warrant a red blood cell transfusion. This simplified transfusion-based approach has unfortunately shifted clinical focus away from strategies to adequately prevent, diagnose, and treat anemia through direct management of the underlying cause(s). While recommendations have been published for the treatment of anemia before elective surgery, information regarding the design and implementation of evidence-based anemia management strategies is sparse. Moreover, anemia is not solely a concern of the preoperative encounter. Rather, anemia must be actively addressed throughout the perioperative spectrum of patient care. This article provides practical information regarding the implementation of anemia management strategies in surgical patients throughout the perioperative period. This includes evidence-based recommendations for the prevention, diagnosis, and treatment of anemia, including the utility of iron supplementation and erythropoiesis-stimulating agents (ESAs).